The Securities Industry in Malaysia: Special Reference to KLSE and the Regulatory Functions of the Securities Commission - Yong, Soon Ching (1997)
This paper deals with the securities industry in Malaysia, in particular the Kuala Lumpur Stock Exchange (KLSE), the new exchange, MESDAQ, which is yet to be established, and the development of the Securities Commission (SC) as the regulatory body supervising the development of the capital market in Malaysia The role of SROs (Self-Regulatory Organisations) will also be examined, in particular the KLSE. The steps taken to achieve a full-disclosure regulatory environment will also be examined, in particular the frontline self-regulated organisations. The regulatory structure overseeing the capital market in MalaYSia will also be examined as will the relevant legislation governing the role of the SC , in the context of law reform and the effectiveness of enforcement actions taken thus far. The overall benefit of this paper lies in its introductory nature into the securities industry in Malaysia and its treatment on the KLSE as well as the sc.